2012
DOI: 10.3389/fphar.2012.00025
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenosides as anticancer agents: In vitro and in vivo activities, structure–activity relationships, and molecular mechanisms of action

Abstract: Conventional chemotherapeutic agents are often toxic not only to tumor cells but also to normal cells, limiting their therapeutic use in the clinic. Novel natural product anticancer compounds present an attractive alternative to synthetic compounds, based on their favorable safety and efficacy profiles. Several pre-clinical and clinical studies have demonstrated the anticancer potential of Panax ginseng, a widely used traditional Chinese medicine. The anti-tumor efficacy of ginseng is attributed mainly to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
232
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 283 publications
(237 citation statements)
references
References 149 publications
(193 reference statements)
4
232
0
1
Order By: Relevance
“…Rg1 has been indicated to have an effect on the function of human diseases via anti-inflammatory and antioxidant defense systems (45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55). The present study demonstrated that Rg1 increased the viability of muscle cells within a starvation model, by inhibiting protein degradation via the AKT/FoxO pathway and promoting protein synthesis by the mTOR pathway.…”
Section: Discussionsupporting
confidence: 54%
“…Rg1 has been indicated to have an effect on the function of human diseases via anti-inflammatory and antioxidant defense systems (45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55). The present study demonstrated that Rg1 increased the viability of muscle cells within a starvation model, by inhibiting protein degradation via the AKT/FoxO pathway and promoting protein synthesis by the mTOR pathway.…”
Section: Discussionsupporting
confidence: 54%
“…Based on their chemical structures, ginsenosides can be classified into three principal structural types, namely, protopanaxadiol, protopanaxatriol, and oleanane. More than 40 ginsenosides have been identified and isolated so far [12,13]. Their nomenclature is based on the designation of Rx and Fx, where R and F refer to the origin of ginsenosides, namely, roots and leaves ("folia") of the species, respectively, and x (x = 0, a1, a2, b1, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Ginsenoside-Rg5 obtained by the processing of ginseng has shown promising anticancer, anti-inflammatory and anti-aging properties (15)(16)(17). There are several reports which demonstrate the activity of ginsenoside-Rg5 against cancer (18,19), dermatis (20), inflammation (21) and neurotrophic disorders (22). This study was performed to investigate the effects of ginsenoside-Rg5 on destruction of cartilage through onset of cartilage matrix damage and death of chondrocytes in OA rat model.…”
Section: Introductionmentioning
confidence: 99%